Next-generation smart carpark - Chezhian, Hemanth (Nanyang Technological University, 2025)
Rapid advancements in technology and the growing significance of sustainable urban development have placed greater emphasis on efficient infrastructure systems, such as smart carparks, in densely populated cities like Singapore. This report explores the development of a next-generation smart carpark system that utilises autonomous parking robots to reduce waiting times, improve efficiency, and enhance the overall user experience of mechanised carpark systems. Based on the examination of prior research into several automated parking systems, gaps have been identified in the incorporation of robotic mobility with real-time allocation algorithms customized for the unique urban landscape of Singapore. Through a series of simulations leveraging real-world data from Geylang Serai Multi-Story carpark in Singapore, critical performance measures were collected and analyzed. Experimental results suggest that the proposed system outperforms the current mechanized system considerably, demonstrating up to a 50% decrease in waiting times and significant improvements in managing simultaneous requests. The findings in the report contribute to the field of sustainable urban planning and development by introducing a feasible and expandable alternative approach to the existing carpark infrastructure.